Linguistic and Cultural Dimensions in the Names of Dwarf Creatures in Indonesian Mythology - Suyuti, Muhammad Wildan; Hendrokumoro (Jurnal Sastra Indonesia, 2025)
This research explores the linguistic and cultural dimensions of dwarf creatures' names in Indonesian mythology. The main focus is analyzing the referential system in naming dwarf creatures and revealing their socio-cultural functions in society. Using a qualitative approach with ethnographic design, this study analyzes data from folklore documentation and ethnographic records. The results show that the referential system in naming dwarf creatures refers to various aspects such as physical characteristics (Uhang Pandak, Manusia Katai), traits and behaviors (Tuyul, Mentek), and geographical locations and mythological origins (Suku Mante, Suku Oni). Culturally, dwarf creatures function as complex social control mechanisms, covering aspects of economic morality (Tuyul), human-nature relationships (Mentek, Orang Bunian), and social identity (Ebu Gogo). This research reveals that the existence of dwarf creatures in Indonesian mythology is not merely a supernatural construction but represents a belief system reflecting the archipelagic society's values, norms, and local wisdom.